PENGARUH KOMITMEN ORGANISASI, AMBIGUITAS PERAN, DAN PROFESIONALISME TERHADAP KINERJA AUDITOR - Galih Chandra Kirana; Sianturi, Heriston; Meifida Ilyas (Jurnal Liabilitas, 2024)
The purpose on the study is to ascertain how professionalism, role ambiguity, and organizational commitment affect auditor performance across all 14 public accounting firms in South Jakarta. A questionnaire was employed in this study as the data gathering tool. Purposive sampling was utilized to determine the research sample. There were 64 participants in this study, including managers, partners, senior auditors, and junior auditors. Multiplle lineare regression analysis techniques are used in the data analysis method. The findings of this study suggest that professionalism and organizational commitment improve auditor performance. Role ambiguity, meantime, has little bearing on the performance fromauditors.. Keywords : Organiozational Commitment; Role Ambiguity; and Professionalism; Auditor Performance.